2015
DOI: 10.1109/jphotov.2015.2458040
|View full text |Cite
|
Sign up to set email alerts
|

Current Enhancement of CdTe-Based Solar Cells

Abstract: We report on the realization of CdTe solar cell photocurrent enhancement using an n-type CdSe heterojunction partner sputtered on commercial SnO 2 /SnO 2 :F coated soda-lime glass substrates. With high-temperature close-space sublimation CdTe deposition followed by CdCl 2 activation, this thin-film stack allows for substantial interdiffusion at the CdSe/CdTe interface facilitating a CdSe x Te 1 −x alloy formation. The bowing effect causes a reduced optical bandgap of the alloyed absorber layer and, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…It seems that this weakness may produce a detrimental effect on the CdSe/CdTe PVs, however, the study of Paudel [1] has demonstrated that employing CdSe as a window layer in the CdSe/CdTe solar cells can enhance the response in the region of long wavelength occurred socalled red shift, and also achieve better efficiency. In spite of & Bing Li libing70@126.com the narrow band gap of CdSe thin films, the element Se in the interface of CdSe/CdTe owns a distinct advantage over element S in the interface of CdS/CdTe, because element Se has a better solubility than S in the CdTe layer [4]. Under the high temperature, ternary compound of CdTe x Se 1-x in the interface of CdSe/CdTe can be formed, when Se diffuses into the absorbed CdTe layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that this weakness may produce a detrimental effect on the CdSe/CdTe PVs, however, the study of Paudel [1] has demonstrated that employing CdSe as a window layer in the CdSe/CdTe solar cells can enhance the response in the region of long wavelength occurred socalled red shift, and also achieve better efficiency. In spite of & Bing Li libing70@126.com the narrow band gap of CdSe thin films, the element Se in the interface of CdSe/CdTe owns a distinct advantage over element S in the interface of CdS/CdTe, because element Se has a better solubility than S in the CdTe layer [4]. Under the high temperature, ternary compound of CdTe x Se 1-x in the interface of CdSe/CdTe can be formed, when Se diffuses into the absorbed CdTe layer.…”
Section: Introductionmentioning
confidence: 99%
“…Under the high temperature, ternary compound of CdTe x Se 1-x in the interface of CdSe/CdTe can be formed, when Se diffuses into the absorbed CdTe layer. Owing to bowing effects [1,4], the newly formed CdTe x Se 1-x presents a lower band gap E g than that of the only CdTe thin film, which may give rise to an excellent response in the realm of long wavelength up to 910 nm. Like others, the same manners are able to be done to increase the photons of short wavelength by reducing the thickness of CdSe thin films, where the absorption of CdSe thin films for photons can be decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the CdSe NC layer is fixed at ≈80 nm (2 layers), the device performance increases first and then decreases linearly with the increase CdS NC layer thickness, indicating the thickness of CdS NC film has a big effect on J sc . It can be concluded that a very thin CdS layer from 0 to 25 nm is attributed to reduce carriers recombination at the interface of ZnO/CdSe, leading to improvement in device performance. However, as the parasitic absorption of CdS layer increases with increasing its thickness, the thick CdS layer from 25 to 100 nm can greatly reduce the spectrum response in short wavelengths, leading to a low J sc .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the energy bandgap as low as 1.32 eV is obtained with x ≈ 0.38 for CdSe x Te 1− x , which is much smaller than 1.5 eV for CdTe . However, devices with a single CdSe ETL may suffer from low V oc and fill factor (FF) due to the large electron injection barrier and interface defects in ZnO/CdSe x Te 1− x , which has been confirmed in the CSS‐processed CdTe solar cells with the SnO 2 /CdSe structure . Thus, new cathode interface strategy should be developed for solution‐processed CdTe NC solar cells.…”
Section: Introductionmentioning
confidence: 93%